Answer:
Step-by-step explanation:
The given arithmetic sequence is
14,30,46,62
The first term of this sequence is
The common distance is obtained by subtracting a subsequent term from a previous term;
d=30-14
The common difference is
d=16
The recursive formula is given by:
We now plug in the known value for the common difference to get;
Answer: what the ather guy said
Step-by-step explanation:
Answer:
x = 22.5
Step-by-step explanation:
2x + 5 > 50.
We do inverse operations sooo:
2x + 5 - 5 > 50 - 5.
50 - 5 = 45.
Then we do 2x ÷ 2 and 45 ÷ 2.
45 ÷ 2 = 22.5.
To check our answer to see if its right we do 22.5 x 2 which equals 45. Then we do 45 + 5 which equals 50. So the sign is wrong it should be greater than or equal to.
Answer:
Step-by-step explanation: 2 plus 5
7 <50
foot 11.71 inches long. What is the explicit formula for the arithmetic sequence? Round to the nearest hundredth, if necessary.
0 6, 7,514 0 35(n-1)
O a. - 9-0 35(n-1)
O a-9-286(n-1)
O a, - 10 31-2 86(n-1)
Answer:
Step-by-step explanation:
The arithmetic sequence has the form:
When a=10.31, n=9, we substitute to get:
Similarly, when n=13 and a=11.71, we get:
Subtract equation 1 from equation 2 to get:
This implies that
Substitute into the second equation to get:
Solve to get
Hence the explicit formula is:
Answer:
A
Step-by-step explanation:
I got it right on edge
a. S159,744.59
b. S48,407.45
c. $580,894.18
d. $330,600.15
$ 159,744.59 will be in the account after 20 years.
Answer: Option A
Step-by-step explanation:
Need to find out the amount present in the account after 20 years. The formula to find out the future value is,
Here
p : amount deposit monthly =$500
r : rate of interest = = 0.0275
n : 12(compound monthly)
t : time =20
By substituting all the given datas in the above equation, we get
Answer:
x = -1 and x = 4
Step-by-step explanation:
Firstly solve the quadratic expression of
2x^2-6x-8 = 0....it gives you the two brackets of.....(2x-8)(x+1)=0
then...you equate the two brackets to 0.separately
2x-8 = 0....which gives you...x = 4...as the first solution..then..;
x+1 = 0....which gives you...x = -1...as the second solution